Validity and Responsiveness of a Modified Balance Error Scoring System Assessment Using a Mobile Device Application in Patients Recovering from Ankle Sprain - Michael S Crowell; Eliot Thomasma; Erin Florkiewicz; Richard Brindle; Megan Roach; Donald Goss; Will Pitt (North American Sports Medicine Institute, 2024)
# Background Static balance is often impaired in patients after ankle sprains. The ability to identify static balance impairments is dependent on an effective balance assessment tool. The Sway Balance Mobile Application (SWAY App) (Sway Medical, Tulsa, OK) uses a smart phone or tablet to assess postural sway during a modified Balance Error Scoring System (mBESS) assessment and shows promise as an accessible method to quantify changes in static balance after injury. # Purpose The primary purposes of this study were to determine the ability to differentiate between those with ankle sprain versus controls (construct validity) and ability to detect change over time (responsiveness) of a mBESS assessment using a mobile device application to evaluate static balance after an acute ankle sprain. # Study Design Case-control study. # Methods Twenty-two military academy Cadets with an acute ankle sprain and 20 healthy Cadets were enrolled in the study. All participants completed an assessment measuring self-reported function, ankle dorsiflexion range of motion (via the weightbearing lunge), dynamic balance, and static balance. Static balance measured with the mBESS using the SWAY App was validated against laboratory-based measures. Cadets with ankle sprains completed their assessment twice: once within two weeks of injury (baseline) and again after four weeks of rehabilitation that included balance training. Independent and paired t-tests were utilized to analyze differences over time and between groups. Effect sizes were calculated and relationships explored using Pearson's correlation coefficients. # Results The mBESS scores measured by the SWAY App were lower in participants with acute ankle sprains than healthy Cadets (*t* = 3.15, *p* = 0.004). Injured participants improved their mBESS score measured by SWAY at four weeks following their initial assessments (*t* = 3.31, *p* = 0.004; Baseline: 74.2 +/- 16.1, 4-weeks: 82.7 +/- 9.5). The mBESS measured by the SWAY App demonstrated moderate to good correlation with a laboratory measure of static balance (*r* = -0.59, *p* \< 0.001). # Conclusion The mBESS assessed with a mobile device application is a valid and responsive clinical tool for evaluating static balance. The tool demonstrated construct (known groups) validity detecting balance differences between a healthy and injured group, concurrent validity demonstrating moderate to good correlation with established laboratory measures, and responsiveness to changes in static balance in military Cadets during recovery from an acute ankle sprain. # Level of Evidence Level 3